2011
DOI: 10.1051/0004-6361/200811333
|View full text |Cite
|
Sign up to set email alerts
|

A very extended molecular web around NGC 1275

Abstract: We present the first detection of CO emission lines in the Hα filaments at distances as far as 50 kpc from the centre of the galaxy NGC 1275. This gas is probably dense (≥10 3 cm −3 ). However, it is not possible to accurately determine the density and the kinetic temperature of this relatively warm gas (T kin ∼ 20-500 K) with the current data alone. The amount of molecular gas in the filaments is large -10 9 M (assuming a Galactic N(H 2 )/I CO ratio). This is 10% of the total mass of molecular gas detected in… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

17
125
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 107 publications
(142 citation statements)
references
References 29 publications
17
125
0
Order By: Relevance
“…bipolar molecular flow in similarly extended filaments that may be accelerated outward by the mechanical energy associated with rising radio bubbles (McNamara et al 2014). Single dish detections of molecular gas coincident with Hα filaments beneath buoyant radio bubbles in the Perseus cluster are consistent with this scenario (Salomé et al 2006(Salomé et al , 2011. Radio jet-driven outflows of molecular gas have also been detected in nearby galaxies (eg.…”
Section: Molecular Gas Clouds Lifted By Radio Bubbles?mentioning
confidence: 78%
See 3 more Smart Citations
“…bipolar molecular flow in similarly extended filaments that may be accelerated outward by the mechanical energy associated with rising radio bubbles (McNamara et al 2014). Single dish detections of molecular gas coincident with Hα filaments beneath buoyant radio bubbles in the Perseus cluster are consistent with this scenario (Salomé et al 2006(Salomé et al , 2011. Radio jet-driven outflows of molecular gas have also been detected in nearby galaxies (eg.…”
Section: Molecular Gas Clouds Lifted By Radio Bubbles?mentioning
confidence: 78%
“…Salomé et al 2008Salomé et al , 2011David et al 2014). In NGC 1275, Salomé et al 2008 found that the CO line ratios indicate optically thick radiation but the observed brightness temperature of the molecular gas clumps is at least an order of magnitude below the expectation for normal, optically thick clouds.…”
Section: Outflowing Molecular Gas Clouds?mentioning
confidence: 95%
See 2 more Smart Citations
“…O'Dea et al 2010;Tremblay 2011). Relative to field galaxies or those in non-CC clusters, BCGs in CCs preferentially harbour radio sources and kpc-scale filamentary forbidden and Balmer emission line nebulae amid 10 9 -10 11 M repositories of vibrationally excited and cold molecular gas (Heckman 1981;Hu, Cowie & Wang 1985;Baum 1987;Heckman et al 1989;Burns 1990;Jaffe & Bremer 1997;Donahue et al 2000;Edge 2001;Edge & Frayer 2003;Salomé & Combes 2003;Egami et al 2006;Salomé et al 2006;Edwards et al 2007; von der Wilman, Edge & Swinbank 2009;Edge et al 2010a,b;Salomé et al 2011;McNamara et al 2014;Russell et al 2014). Low to moderate levels (∼1 to 10 M yr −1 ) of star formation appear to be ongoing amid these mysteriously dusty (O'Dea et al 2008;Quillen et al 2008;Edge et al 2010a,b;Mittal et al 2011;Rawle et al 2012;Tremblay et al 2012b), polycyclic aromatic hydrocarbon (PAH)-rich (Donahue et al 2011) cold reservoirs on 50 kpc scales in clumpy and filamentary distributions (e.g.…”
mentioning
confidence: 99%